APPLICATION OF ASSIGNMENT METHOD WITH SEVIMA EDLINK TO IMPROVE STUDENT'S DISCIPLINE AND MATHEMATICS LEARNING ACHIEVEMENT - Mahayukti, Gst Ayu; Sudiarta, I Gusti Putu; Putra, I Dewa Gede Limarta Yusadi (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2022)
Due to the pandemic, teachers need to make breakthroughs in carrying out online learning by utilizing the right online learning media, one of which is the Sevima Edlink application, because Sevima EdLink is an application that can be accessed via a computer or Android, and is free and without installation.This study aims to improve students' achievement and discipline in learning mathematics through the application of the sevima edlink assignment method in online learning on matrix material and matrix transformation. This research is a classroom action research covering three cycles with four stages, namely planning, implementation, observation, and reflection. The subjects of this study were all 36 students of class XI MIA 2 SMA Negeri 1 Seririt. Data were collected through mathematics learning achievement tests and learning discipline questionnaires. The results show that students' mathematics learning achievement in each cycle has increased. Cycle I, the average student's mathematics achievement test was 70.70; in the second cycle of 74.48,; and in the third cycle of 76.33. Student learning discipline also increased, in the first cycle the average value of mathematics learning discipline obtained by students was 77.39 in the high category; in the second cycle the value of the discipline of learning mathematics obtained by students was 79.79 in the high category; and in the third cycle the value of the discipline of learning mathematics obtained by students was 82.17 in the high category. So it can be said that the application of the sevima edlink assignment method in online learning can improve mathematics learning achievement and student learning discipline.